TISSUE GRAFTS IN VITILIGO SURGERY – PAST, PRESENT, AND FUTURE - Khunger, Niti (Medknow Publications, 2009)
Vitiligo, characterized by depigmented macules is a common disorder with a high psychosocial impact, particularly in darker skins. Surgical methods become important in cases where medical therapy fails to cause repigmentation or in cases of segmental vitiligo where the response to surgery is excellent. The basic principle of surgical treatment is autologous grafting of viable melanocytes from pigmented donor skin to recipient vitiliginous areas. Various grafting methods have been described including tissue grafts and cellular grafts. Stability of the disease is the most important criterion to obtain a successful outcome. Counseling of the patient regarding the outcome is vital before surgery. The technique and followup management of the tissue grafts has been described in detail in this review.